"We Show What Is Concealed": Russian Soft Power in Germany. Issue 3 (4th May 2021) - Decker, Philip K.
ABSTRACT: Using a modified theoretical model derived from the work of Joseph Nye, this paper argues that Russian media have conducted a soft power campaign in Germany that targets that country's Russian-speaking population. Among a portion of the target group, Kremlin-funded outlets have succeeded in encouraging skepticism of German culture and authorities while presenting Russian culture and government as representative of a superior alternative value system. These conditions have helped generate political disruption (significant Russian-German support for the right-wing populist party Alternative für Deutschland) and physical unrest (a protest over the purported rape of a Russian girl by migrants).